Sanctuary: Rage of the Ancients - Book 12 - Crane, Robert J. (USA Ostiagard Press, 2023)
Cyrus Davidon and his company of Sanctuary are at an end. Split from each other, facing their greatest adversary, cut off from the powers of magic that reigned in days past - the situation is most dire. Yet hope still lives while they remain alive. And alive they are, though barely, and hounded to the ends of the earth by enemies old and new. Only a small amount of time remains before the enemy strikes the final blow, and Cyrus must gather his friends, and find away to beat this unstoppable evil... ...Or else the world itself will come to an end.
Keywords: Magic -- Fiction; Good and evil -- Fiction; Fantasy fiction